Metode Fun Creative Learning dalam Pengajaran Pendidikan Agama Islam di Sekolah Dasar Islam - Rakha Ryanki Farhan; Ulil Amri Syafri; Abas Mansur Tamam (UMSU, 2022)
Teachers play an important role in the education system as they advance student learning and choose learning management methods that suit the needs of their students. The teacher's contribution to learning also affects educational performance. One of the disciplines taught in public and private schools to advance the goals of national education is Islamic Religious Education (PAI). Consequently, we must concentrate on the objectives of religious education as a component of the general education system. Teachers must foster creativity in their students by encouraging critical thinking and taking initiative. The purpose of this study was to determine the fin creative learning method in teaching PAI at Fajar Hidayah SDIT. The research method used is in the form of a qualitative description. Collecting data by taking the results of the learning observation report that took place and then giving some questions to the respondents, namely the 6th grade PAI teacher. SDIT Fajar Hidayah has appropriate learning in this study, where teachers are required to teach all learning creatively and fun for all students.